Relationship between Serum Uric Acid Levels and Severity of Hypertension in Adult Patients - Huma Naeem Tareen, Aftab Hussain Khan, Asim Iqbal, Afshin Aman, Muhammad Ali Khawaja, Abid Hussain, (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To establish the correlation between serum uric acid and the level of hypertension in adult patients who report to a tertiary care hospital. Study Design: Descriptive cross sectional study. Place and Duration of Study: Tertiary care Teaching Hospital (Department of Cardiology and Medicine, Bolan Medical College Hospital, Quetta), between February 2023 to August 2023. Methodology: Non-probability consecutive sampling was used to enroll 369 adult patients who had diagnosed essential hypertension. Blood pressure was measured by means of standardized protocol and hypertension was diagnosed into stage 1 and stage 2 by using standardized protocols. Estimation of serum uric acid through enzymatic colorimetric technique was done on venous blood samples. Hyperuricemia was considered to be the serum uric acid level exceeding 7.0 mg/dL in men and 6.0 mg/dl in women. The SPSS version 25 was used to analyze data. Quantitative variables have been presented in the form of mean, SD and qualitative variables have been presented in the form of frequencies and percentages. Appropriate statistical tests were used to determine the relationship between levels of serum uric acid and the level of hypertension with a p-value of 0.05 taken as a statistically significant value. Results: The average age of the participants was 52.611.4. Sixty-one point five percent of the patients had hypertension 2 in stage 2. Stage 2 hypertensive patients had significantly high levels of mean serum uric acid level when compared to patients with stage 1 hypertension (7.3 ± 1.5 mg/dL vs 6.1 ± 1.3mg/dl; p<0.001). Hyperuricemia was high in patients with hypertension of stage 2. Conclusion: High serum uric acid is closely related with intense hypertension. Serum Uric acid could be an easy and affordable indicator of high-risk patients in resource-constrained environments with regard to severe hypertension. Keywords: High blood pressure; Urine level; Overuricemia; Blood pressure intensity.